A maximum capture width tracking controller for ocean wave energy converters in irregular waves. (15th July 2016) - Hardy, P.; Cazzolato, B.S.; Ding, B.; Prime, Z.
Abstract: A maximum capture width tracking (MCWT) controller for ocean wave energy converters is presented. The MCWT controller is a maximum power point tracking (MPPT) controller modified to account for incoming wave conditions as well as WEC power output. The MCWT controller will be applied to latching control of an oscillating water column with Wells turbine, optimising the latching time based on sea state. The performance of the proposed MCWT latching controller will be compared to that of an MPPT latching controller in both stationary and transitioning sea states. In stationary seas, it will be shown that both controllers can optimise capture width to within the bounds of certainty that the optimal capture width can be known for a WEC in stochastic waves. In transitioning seas, it will be shown that the MCWT controller is robust to a changing environment, whereas the MPPT controller is not. Abstract : Highlights: A model independent controller for ocean wave energy converters (WECs) is presented. WEC capture width is shown to be a Gaussian random variable. The controller is shown to optimise WEC capture width in stationary seas. The controller is robust to environmental changes in non-stationary sea states. The controller is shown to be effective in bi-modal sea states.